Relation of serum cytokine concentrations to cardiovascular risk factors and coronary heart disease. Issue 3 (September 1997) - Mendall, M. A.; Patel, P.; Asante, M.; Ballam, L.; Morris, J.; Strachan, D. P.; Camm, A. J.; Northfield, T. C.
Abstract : OBJECTIVE: To determine whether serum concentrations of the cytokines tumour necrosis factor alpha (TNF alpha) and interleukin 6 (IL-6), which regulate C reactive protein, are associated with cardiovascular risk factors and prevalent coronary heart disease. DESIGN: A population based cross sectional study. SUBJECTS AND METHODS: 198 men aged 50 to 69 years were part of a random population sample drawn from south London. Serum cytokine and C reactive protein concentrations were determined by enzyme linked immunosorbent assay. The presence of coronary heart disease was determined by Rose angina questionnaire and Minnesota coded electrocardiogram. RESULTS: Serum TNF alpha concentrations were positively related to body mass index and Helicobacter pylori infection, but inversely related to alcohol consumption. IL-6 concentrations were positively associated with smoking, symptoms of chronic bronchitis, age, and father having a manual occupation. TNF alpha was associated with increased IL-6 and triglycerides, and reduced high density lipoprotein cholesterol. IL-6 was associated with raised fibrinogen, sialic acid, and triglycerides. ECG abnormalities were independently associated with increases in IL-6 and TNF alpha, each by approximately 50% (P < 0.05 for TNF alpha, P < 0.1 for IL-6). The corresponding increases in men with an abnormal ECG or symptomatic coronary heart disease were 28% for TNF alpha and 36% for IL-6 (P = 0.14 for TNF alpha and P < 0.05 for IL-6). CONCLUSIONS: This study confirms that many of the phenomena with which C reactive protein is associated, are also associated with serum levels of cytokine, which may be the mechanism.